-6(4k-7)-4k=-5-3(7k-4)

Simple and best practice solution for -6(4k-7)-4k=-5-3(7k-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(4k-7)-4k=-5-3(7k-4) equation:


Simplifying
-6(4k + -7) + -4k = -5 + -3(7k + -4)

Reorder the terms:
-6(-7 + 4k) + -4k = -5 + -3(7k + -4)
(-7 * -6 + 4k * -6) + -4k = -5 + -3(7k + -4)
(42 + -24k) + -4k = -5 + -3(7k + -4)

Combine like terms: -24k + -4k = -28k
42 + -28k = -5 + -3(7k + -4)

Reorder the terms:
42 + -28k = -5 + -3(-4 + 7k)
42 + -28k = -5 + (-4 * -3 + 7k * -3)
42 + -28k = -5 + (12 + -21k)

Combine like terms: -5 + 12 = 7
42 + -28k = 7 + -21k

Solving
42 + -28k = 7 + -21k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '21k' to each side of the equation.
42 + -28k + 21k = 7 + -21k + 21k

Combine like terms: -28k + 21k = -7k
42 + -7k = 7 + -21k + 21k

Combine like terms: -21k + 21k = 0
42 + -7k = 7 + 0
42 + -7k = 7

Add '-42' to each side of the equation.
42 + -42 + -7k = 7 + -42

Combine like terms: 42 + -42 = 0
0 + -7k = 7 + -42
-7k = 7 + -42

Combine like terms: 7 + -42 = -35
-7k = -35

Divide each side by '-7'.
k = 5

Simplifying
k = 5

See similar equations:

| 105+Y=105 | | 6y+2=-y+32 | | -9-5x=-19 | | 2(b-21)=41-3(b-4) | | (3x-7y)(x+3y)= | | 5x-3x-10=-34 | | 3x-8=-5x-20 | | -(v+4)=-4-3v | | -9+k+3k=9-2k | | 14x-21=12x+29 | | 3x+2(x+10)=170 | | N*(2n-4)=17 | | 28x+52=25 | | 3x^2+2x^2=0 | | 2(v+8)=8(-v-8) | | 5+7x=96 | | 7a+2=1 | | 1.5-.4y=3.3 | | 6x^2-44x=-63 | | -(7v+7)=5-4v | | Q+83=902 | | p=6+7p | | -38=2(-43d-24) | | 9c-6-6c=16 | | 4(y+1)=6y-8 | | -10-3h=8h+3+9 | | (4m-120)= | | -8(r-6)=-8-6(-2+5r) | | -13m+7m=18-66 | | 8.7x=156.6 | | 5x-(3x-2)=18 | | -8x-8=3x+25 |

Equations solver categories